(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The growth of modern urban planning places high demands on the quality of raw materials, including concrete, which are directly related to the quality of building structures. Therefore, the production of quality concrete, the creation of new cement compositions and energy-saving technologies are among the priorities. At the same time, it is important to improve the physical and chemical properties of concrete based on the use of local mineral raw materials. The article presents the analysis of active mineral admixtures and the results of concrete tests using tuffite.